Contamination Analysis of Escherichia coli on Broiler Chicken Meat in Traditional Markets of Medan City - Siregar, Julinda; Umar, Sayed; Nevy Diana Hanafi (Talenta Publisher, 2021)
Escherichia coli (E. coli) is a gram-negative bacteria that can reduce meat quality and cause diarrhea if the amount is too much. This study investigates the presence of E. coli contamination in chicken meat sold in traditional markets in Medan. This research was conducted using the purposive sampling method and collected samples from 30% of each nine traditional markets with 32 samples. The traditional markets in Medan, namely Petisah, Central, Sei Kambing, Kampung Lalang, Kwala Bekala, Helvetia, Kampung Baru, Kemiri and Padang Bulan. Research was conducted by using the CFU / ml method with chromocult media. Samples were analyzed in the laboratory of the Regional Veterinary Disease Investigation Center Region 1 Medan. The results showed 32 samples of chicken meat had exceeded the maximum limit of microbial contamination. The highest total microbial average was in the Kampung Lalang market, 3.49 Log CFU / g, and the lowest was in the Kemiri market of 2.79 Log CFU / g. Based on the research results, it was found that the meat in the traditional markets of Medan was all contaminated with E. coli and had passed the maximum limit of bacterial contamination.